Surface functionalization of magnetic nanoparticles via palladium‐catalyzed Diels‐Alder approach. Issue 46 (7th December 2018) - Maleki, Ali; Taheri‐Ledari, Reza; Soroushnejad, Mahya
Abstract: Metal nanoparticles are currently being used as substantial catalysts for a number of classical chemical transformations. In contrast, performing novel biochemical reactions with the help of nano‐organocatalysts is highly underdeveloped area in chemical synthesis. In order to prepare an efficient nano‐organocatalyst, facilitated stable covalent bonding would be achieved by using Diels‐Alder reactions on the surface of magnetic nanoparticles. Herein, we report the synthesis of magnetic nano‐organocatalysts by using Fe3 O4 nanoparticle coated by SiO2 network and functionalized with vinylsilane, as dienophile moiety of Diels‐Alder reactions. In this work, palladium(II) is used as an instrumental catalyst for Diels‐Alder reaction, as well. Abstract : Surface modification of iron oxide nanoparticles has been reported via simple one‐step mechanism of Diels‐Alder approach. Magnetic core coated by silicate network and modified with vinylsilane, was used as dienophile moiety of Diels‐Alder reaction, for the first time. Palladium(II) was used as an instrumental catalyst for Diels‐Alder reaction, as well. The obtained products would be used as nano‐organocatalysts in biochemical conjugation reactions which include sensitive biological compounds.